The impact of religion: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Witte, John; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2020)
Late modern pluralistic societies are characterised by an infinitely multi-coloured individuality of their citizens and a wealth of associations and groups. This »plurality«, which is difficult to grasp, is welcomed by many people as a source of freedom, but feared by some people inside and many observers outside as a social chaos. However, this plurality is countered by a limited number of so-called »social systems«, which are to a large extent characterised by organisational, institutional and normative structures and weight. The overwhelming majority of the contributions in this volume deal with the Christian religion, as pluralistic societies today thrive substantially in Christian environments. Contributions by Peter Carnley, Gregor Etzelmüller, Johannes Eurich, Jennifer Herdt, Admiel Kosman, Piet Naudé, Waihan Ng, Friederike Nüssel, Bernd Oberdorfer, Martin Percy, Stephen Pickard, Raja Sakrani, William Schweiker, Philipp Stoellger, Milton Wan, Renee Ip, and Michael Welker. [Der Einfluss der Religion auf Charakterbildung, ethische Erziehung und Kommunikation von Werten in spätmodernen pluralistischen Gesellschaften] Spätmoderne pluralistische Gesellschaften sind von einer unendlich vielfarbigen Individualität ihrer Bürgerinnen und Bürger und einer Fülle von Zusammenschlüssen und Gruppierungen geprägt. Diese schwer zu fassende »Pluralität« wird von vielen Menschen als Quellgrund der Freiheit begrüßt, von manchen Innenstehenden und vielen Außenstehenden aber auch als soziales Chaos gefürchtet. Doch dieser Pluralität steht eine begrenzte Zahl von sogenannten »sozialen Systemen« gegenüber, die in hohem Maße organisatorisch, institutionell und normativ geprägt sind. Die überwältigende Mehrzahl der Beiträge diese Bandes behandeln die christliche Religion, da pluralistische Gesellschaften heute wesentlich in christlichen Umgebungen gedeihen. This book on the influence of religion on the ethos of pluralistic societies is part of a series of ten international research projects with contributions from all continents. The influences of the market, law, science, politics, media, family, education, medicine and defense will also be examined.
Keywords: Aufsatzsammlung; Konferenzschrift; Religiöse Erziehung; Wertorientierung; Sittliche Erziehung; Charakterbildung; Pluralistische Gesellschaft; Christliche Erziehung